Identification of tampering methods among 12,385 Arabian camels using different diagnostic imaging techniques - Mohamed Tharwat; Abdulla Al-Hawas (Open Veterinary Journal)
Background: Tampering is an illegal manipulation of Arabian (dromedary) camels for cosmetic purposes and to increase their market value. Because of the tremendous prizes awarded to the owners of the winning camels, methods of illegal tampering were frequently developed in camel beauty festivals. The detection of such practices constitutes a significant challenge for veterinarians supervising these festivals. One of these challenges is the large numbers of examined camels at beauty festivals. The second is the disappearance of injected hormones in the blood from days to months after their preliminary injection. Such challenges may be faced by using well-trained and professional veterinarians as well as developing new recent and advanced laboratory techniques that can discover traces of injected hormones or even blood proteins released as a result of specific hormone injection.